Synthesis and Optical Properties of Colloidal Gold Nanoparticles for Biomedical Applications - Lien, Nghiem Thi Ha; Hoa, Vu Xuan; Duong, Vu Thi Thuy; Tinh, Nguyen Van; Nhung, Tran Hong (Communications in Physics, 2011)
The gold nanoparticle solutions are well known as an extremely sensitive biomedical analytical tool due to the strong dependence of their absorption in the visible range on the environment. In this work, the colloidal nano golds were synthesized from metal precursor chloroauric acid (HAuCl4) using trisodium citrate dehydrate (C6H5O7Na3) as reducing and stabilizing agents. The optical characterization - absorption of colloidal gold solution have been investigated under the different synthetic conditions such as: reducing agent concentration, concentration of auric ion, pH, duration of reaction and aging time. The results show that the absorption and the stability of the colloidal gold nanoparticles depend robustly on the synthetic conditions and pH of environment.